Jawabanmu

2014-06-19T18:12:57+07:00
D = 0
D = b² - 4ac
maka
(2m + 1)² - 4.2.m = 0
4m ² + 4m + 1 - 8m = 0
4m² - 4m + 1 = 0
( 2m - 1 ) ( 2m - 1) = 0
jadi,
2m - 1 = 0        atau  2m - 1 = 0
2m = 1                      2m = 1
m = 1/2                        m = 1/2
1 3 1
Jawaban paling cerdas!
2014-06-19T19:20:03+07:00
2x² - (2m+1)x + m = 0
a. saling berlawanan
     x1 = -x2
     x1 + x2 = 0
         -b/a  = 0
       2m + 1 = 0
             2
       m + 1/2 = 0
       m = -1/2
b. saling berkebalikan

     x1 = 1/x2
     x1x2 = 1
       c/a = 1
       m/2 = 1
         m = 2
2 5 2